Exploring the potential of acupuncture as a complementary therapy for post-COVID skin hyperpigmentation: a case report - Xue, Yuan; Li, Xingyao; Duan, Yingying; Gao, Qi; Zhao, Yanhong; Wu, Xili; Wu, Zhongheng (Frontiers in Medicine, 2025)
BackgroundPost-COVID sequelae include skin abnormalities with nonspecific characteristics, making disease-specific diagnosis challenging. Conventional treatment primarily relies on modern medical approaches, and the potential of complementary therapies, such as acupuncture, remains underexplored.Case reportThis case describes a patient who developed abnormal skin pigmentation following a COVID-19 infection and was initially diagnosed with five different conditions. After a prolonged period of unsuccessful treatment with conventional medicine, the patient received complementary therapy, leading to significant symptom improvement.ConclusionComplementary therapies, such as acupuncture, may prove beneficial in treating skin conditions that lack a definitive diagnosis, as demonstrated in this case.